2014
DOI: 10.1007/s13277-014-1761-z
|View full text |Cite
|
Sign up to set email alerts
|

High sensitivity of touch imprint cytology in young patients with invasive lobular carcinoma of the breast

Abstract: Invasive lobular carcinoma (ILC) of the breast is a rare type of breast cancer. Metastatic ILC is difficult to identify in sentinel lymph nodes (SLNs) because of its low-grade cytomorphology and its tendency to resemble lymphocytes. Touch imprint cytology (TIC) is a rapid method for evaluating SLNs intraoperatively. We sought to evaluate this technique in the identification of SLN metastases in ILC. A total of 230 SLNs from 88 patients diagnosed with ILC were examined with TIC, and the results were compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…TIC is considered a more tissue conserving and less expensive method compared to FS with comparable accuracy [ 6 ]. The sensitivity of the TIC test on SLN in breast cancer is not consistent between studies, and seems to vary according to different tumor types, tumor size and the age of the patient [ 4 10 ]. Especially metastasis of invasive lobular carcinoma in the SLN is reported to be more difficult to identify on pathological examination compared to ductal carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…TIC is considered a more tissue conserving and less expensive method compared to FS with comparable accuracy [ 6 ]. The sensitivity of the TIC test on SLN in breast cancer is not consistent between studies, and seems to vary according to different tumor types, tumor size and the age of the patient [ 4 10 ]. Especially metastasis of invasive lobular carcinoma in the SLN is reported to be more difficult to identify on pathological examination compared to ductal carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, a higher probability of false-negative results has been recorded and the presence of micrometastasis cannot be excluded 1113. Sensitivity also depends on the histologic type of the tumor, with lower rates of detection for lobular carcinoma (LC) in comparison with the more common ductal type 14,15. Additional immunohistochemical staining may aid in the detection of micrometastases even in LC and contributes to the increase of IC sensitivity 16.…”
Section: Introductionmentioning
confidence: 99%
“…Low sensitivity of IIC in our Institute was probably due to the different preparation and fixation technique used for IIC at our Institute. In our study, the sentinel LN fat capsule was not always completely removed as described in other studies [ 21 ]. Furthermore, all our imprints were air-dried and stained with Hemacolor quick stain.…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, all our imprints were air-dried and stained with Hemacolor quick stain. Other studies with a higher sensitivity of IIC reported the use of two techniques combined, one being air drying and quick staining and the other an immediate 3-min fixation with ethanol and staining with hematoxylin and eosin (HE) [ 20 , 22 ], or only using 3-min ethanol fixation with HE staining [ 21 ].…”
Section: Discussionmentioning
confidence: 99%